Protocolo de comunicação GPS-Servidor utilizando MQTT - Cangianelli, Daniel Negreiros (2019)
Vehicle security services are items of interest to the population due to the great lack of security faced in the country. The use of information technology to develop solutions has great potential in the market. With the evolution of IoT, the MQTT protocol, for example, is a feature that offers low power consumption, minimized data packets and efficient information distribution to one or several receivers. Thus, the objective of the work was to develop a protocol, standardizing communication between MQTT-based server and crawler device. A server was configured to function as an MQTT broker, code was developed for the ESP8266 board to subscribe and to publish vehicle location messages on a specific broker topic via the Mosquito interface, after which programming for an application to subscribe to the topic and read and store location values. Then this same application was configured to function as a servlet and respond to a GET HTTP request, returning the stored values. Finally, a mobile application for Android devices was developed, which received implementations to request data and present vehicle location to the user with a list of all their vehicles and their locations on the map.